Allogeneic hematopoietic cell transplantation is potentially curative in mantle cell lymphoma: results from a single institution study. Issue 2 (28th January 2019) - Sandoval-Sus, Jose D.; Faramand, Rawan; Chavez, Julio; Puri, Sonam; Parra, Paola; Sokol, Lubomir; Kharfan-Dabaja, Mohamed A.; Shah, Bijal; Ayala, Ernesto
Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is the only curative treatment for mantle cell lymphoma (MCL). We retrospectively analyzed outcomes of 36 patients, median age of 54 (41–68) years, who underwent allo-HCT, mostly (66%) receiving a myeloablative (MAC) regimen. Median overall survival (OS) was 86 months and 5-year OS was 54%. Median progression-free survival (PFS) was 54 months and 5-year PFS was 49%. Cumulative incidence (CI) of non-relapse mortality (NRM) and 2-year progression were 20.1 and 22.1%, respectively. Day +100 CI of grade II–IV acute graft-versus-host disease (GVHD) was 38.1%; 2-year CI of moderate/severe chronic GVHD was 31.7%. Seven patients received allo-HCT as frontline consolidation and had better OS (median = not reached versus 54 months, p  = .045). Notwithstanding the small sample size and retrospective study design, our findings suggest a role for allo-HCT in selected MCL patients. Future prospective studies would be needed to better define the role of allo-HCT in this disease.